Comparative Analysis of Stock Prices, Stock Returns and Stock Trading Volume Activities Before and After the 2024 Presidential Election Event Study on JII Indexed Issuers on the Indonesia Stock Exchange - Fitriyani, Yuniar; Widodo, Teguh (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
The purpose of this study is to analyze the comparison before and after the 2024 presidential election related to the reaction of the capital market that is proxied by stock prices, stock returns, and JII stock trading volume activities. The election event, one of which chose a presidential candidate, occurred on February 14, 2024, as the event date of the study and the window period in this study was determined 30 days before and 30 days after the event date. Including quantitative research because the data taken is secondary data sourced from idx.co.id where the population is also a sample of 30 leading sharia-based companies with good performance according to the Indonesia Stock Exchange. The findings of the study indicate that there is no significant difference in the average stock price, average stock return, or average TVA before and after the presidential election in the 2024 election